MOTIF PEMBAGIAN MERCHANDISE PADA KAMPANYE PILIHAN WALIKOTA SURABAYA 2020 - Irianti, Yunia Mulia (Fakultas Politik Pemerintahan, 2021)
The election of the mayor is part of Indonesia's democratic party. This momentum is highly anticipated by various circles of society. Especially during the candidate campaign period. This is a golden opportunity for candidate pairs to attract support. One of them is by distributing merchandise to the public. Surabaya is the city that its leader has been waiting for as the place for Tri Risma Harini. His success in the Surabaya office has set a brilliant track record during his tenure. Therefore, the candidates for mayor and deputy mayor who are elected in the next period have the task of making Surabaya better. The 2020 Surabaya city election campaign period is a competition between the two candidates for mayor and candidate for deputy mayor. During the campaign period, each prospective candidate competed to attract the attention of the public. Based on this phenomenon, the analysis of the research theory uses Alfred Schutz's theory of motives. Analysis of the division of the two types of motives, namely because of the motive and so that the motives can see the motives of the distribution of merchandise in the 2020 Mayor of Surabaya's election campaign. This research uses qualitative methods with observation, interview and documentation data. Qualitative data were analyzed by stages of reduction, appearance, conclusion. The results showed that the motive for the distribution of merchandise in the 2020 mayor of Surabaya's election campaign was based on motives.